An Intertemporal Urban Economic Model with Natural Environment - Jian Zhang; Hiroyuki Shibusawa; Yuzuru Miyata (European Regional Science Association (ERSA), 2005)
We are surely faced with the unavoidable problem as an element of important restrictions of development of human beings. It must be required to be solved immediately. It also brought the economic concerns to academic fields long ago. The positive and negative impacts of environmental and ecological changes are concerned the shift to a circulated type society from the conventional society. It is required by the end of today when the environmental problem in a global scale is aggravating. The view of the compact city of energy and resources saving is observed in recent years. The research on the balance of environmental load and urban growth needs to attract attention. In this paper, we consider a problem concerning the relationship between the spatial efficiency and the sustainability in an urban system. An urban model with natural environment is constructed to examine the possibility of such future urban forms. The idea of compact city offers us an important concept for sustainability. Our approach is based on the urban economic framework. Urban models, which have been developed since the 1970s, are classified into two categories, static and dynamic models. We adopt the framework of the dynamic urban model. In our study, the dynamic urban economic model with natural environment is built. The optimal control is applied into our numerical computation and the simulation analysis of the model is performed under several scenarios.
Keywords: 330